Implementasi Kurikulum Merdeka di Pesantren Fathurrobbaaniy Cisoka: Membentuk Generasi Berkarakter dan Kompetitif dalam Pendidikan Islam - Koimah, Siti Mariyatul; Zahra, Nur Amalia; Putri, Mas Fierna Janvierna Lusie (CV. Kurnia Grup, 2024)
The implementation of the Independent Curriculum at Pesantren Fathurrobbaaniy Cisoka aims to shape a generation that is both character-driven and competitive within Islamic education. This study examines how the flexible and contextual approach of the Independent Curriculum can be applied in a pesantren environment to address the challenges of globalization and modernization. Using qualitative methods including interviews, observations, and documentation, this research explores the strategies employed by the teaching staff in integrating this new curriculum. The results indicate that the Independent Curriculum provides flexibility in designing learning programs that are more relevant to local needs and the potential of the students. Pesantren Fathurrobbaaniy successfully integrates moral values and 21st-century skills into the learning process, enhancing student participation and interest in both academic and non-academic activities. Challenges in adapting traditional teaching methods and improving parental understanding were addressed through comprehensive socialization and training. The implementation of the Independent Curriculum at this pesantren shows significant positive impacts on improving the quality of education and shaping students with strong moral character and high competitiveness.